Local Wisdom Anti-Hoax Values in Sundanese Proverb: A Semiotic Approach - Aan Ramadhansyah Rahayu (Jurnal Bahasa Inggris Terapan, 2018)
This study analyzed the wisdom values contained in Sundanese proverb that relates to anti-hoax values. This study was conducted to bring backcharacter and philosophy of Sundanese community which contained in the Sundanese proverb, in order not to be forgotten and still applied in everyday life. The source of the data that collected in this study is derived from Babasan and PribahasaSunda Book. The method used in this study is a qualitative method with semiotic analysis approach of Roland Barthes. The purpose of this study is to analyze and describe anti-hoax values that contain in Sundanese proverb. The result shows that the proverb of Sundanese containsanti-hoax values. Those values arevalues of accuracy in reading Information and values of honesty.